Insulin-positive cells in liver and exocrine part of pancreas in animals with experimental diabetes mellitus - M. B. Baykenova; V. A. Chereshnev; K. V. Sokolova; I. F. Gette; V. V. Emelianov; I. G. Danilova (Бюллетень сибирской медицины, 2021)
Aim. To compare the number of insulin+ cells in the liver and exocrine part of the pancreas with the type of  experimental diabetes, blood glycose and glycated hemoglobin (HbA1с) level and with the number of Pdx1+ cells.Materials and methods. The experiment was carried out on 25 male Wistar rats (weighting (303.0 ± 25.3) g) that were divided into 3 groups: the first group consisted of intact animals, the second had animals with experimental diabetes type 1, and the third with animals with experimental diabetes type 2. Biochemical, immunohistochemical, ELISA methods and statistical analysis were used.Results. Insulin+ and Pdx1+ cells of rats with experimental diabetes were found in the liver and exocrine part of pancreas. The highest number of insulin+ cells in the liver was detected in type 2 diabetes (T2D). A strong positive correlation between the number of insulin+ cells in the liver and level of glycosylated hemoglobin in theblood was revealed in both type 1 and type 2 diabetes.Conclusion. Insulin+ cells are detected in the liver and acinar part of pancreas of both intact rats and rats with experimental diabetes. Group with T2D is characterized by the highest number of insulin+ cells in the livercompared with type 1 diabetes (T1D). The localization of insulin+ cells in the liver changes depending on the  type of diabetes. In T2D insulin+ cells are located in all parts of liver acini, meanwhile in animals with T1D such cells are mainly detected in the periportal area. The expression of Pdx1+ in acinar cells of pancreas and liver cells is likely a mechanism for their reprogramming into insulin+ cells in experimental diabetes mellitus.